How can activists fight digital pollution in adverse brand contexts? - Stüben, Elena Gina Margaux (2021)
Digital pollution concerns the pollution of new technologies through the global functioning of the Internet network, the manufacture of digital tools, and their uses. Digital ecology is a central axis to develop to rationalize the usage, promote the reduction of energy consumption, and guarantee the ecological transition. This work explores how activists in the digital ecology field can overcome challenges and develop strategies to promote digital pollution among consumer goods companies and their ecosystems, fostering a more sustainable digital use. To do so, the author has used a qualitative method based on four interviews. The findings reveal that adverse brand contexts can partner to promote digital ecology. Activists act as a consultant for brands, teaching them about their role in the concept, bringing mutual benefit in terms of knowledge and opportunities and leading to a partnership.